In Vivo Evaluation of the Effects of B-Doped Strontium Apatite Nanoparticles Produced by Hydrothermal Method on Bone Repair - Oztekin, Faruk; Gurgenc, Turan; Dundar, Serkan; Ozercan, Ibrahim Hanifi; Yildirim, Tuba Talo; Eskibaglar, Mehmet; Macit, Cevher Kursat (Mdpi, 2022)
In the present study, the structural, morphological, and in vivo biocompatibility of un-doped and boron (B)-doped strontium apatite (SrAp) nanoparticles were investigated. Biomaterials were fabricated using the hydrothermal process. The structural and morphological characterizations of the fabricated nanoparticles were performed by XRD, FT-IR, FE-SEM, and EDX. Their biocompatibility was investigated by placing them in defects in rat tibiae in vivo. The un-doped and B-doped SrAp nanoparticles were successfully fabricated. The produced nanoparticles were in the shape of nano-rods, and the dimensions of the nano-rods decreased as the B ratio increased. It was observed that the structural and morphological properties of strontium apatite nanoparticles were affected by the contribution of B. A stoichiometric Sr/P ratio of 1.67 was reached in the 5% B-doped sample (1.68). The average crystallite sizes were 34.94 nm, 39.70 nm, 44.93 nm, and 48.23 nm in un-doped, 1% B-doped, 5% B-doped, and 10% B-doped samples, respectively. The results of the in vivo experiment revealed that the new bone formation and osteoblast density were higher in the groups with SrAp nanoparticles doped with different concentrations of B than in the control group, in which the open defects were untreated. It was observed that this biocompatibility and the new bone formation were especially elevated in the B groups, which added high levels of strontium were added. The osteoblast density was higher in the group in which the strontium element was placed in the opened bone defect compared with the control group. However, although new bone formation was slightly higher in the strontium group than in the control group, the difference was not statistically significant. Furthermore, the strontium group had the highest amount of fibrotic tissue formation. The produced nanoparticles can be used in dental and orthopedic applications as biomaterials.
Keywords: endodontic surgery; bone repair; osteoblast; strontium apatite; nanomaterial